Producción de un programa piloto de radio testimonial, dirigido a estudiantes de nivel medio para que se conozcan la experiencia de las madres adolescentes. - Naranjo Morales, Lady Cumanda (2014)
Thesis focused on: "Production of a pilot testimonial Radio program, aimed at middle school students, to get them to know experience of teenage mothers". Its main objective is to disseminate the difficulties encountered by teenager mothers; to, this way, they have got in count experiences of unwanted pregnancies. The problem was identified globally, taking variations depending on the society in which they found themselves, as the lack of information on contraception methods and the subsequent responsibilities that become with pregnancy and motherhood at an early age, higher incidences were found in countries with more poverty and less access to educational institutions. The little of information offered to teenagers about the consequences of irresponsibility within an active sex life is one of the causes leading to unwanted pregnancies, whence, through the production of a pilot testimonial Radio program we all may know about sexuality from the experiences of young people who went through similar situations that many teenagers face nowadays.